The mistress of Tall Acre [large type] : a novel - Frantz, Laura (Thorndike Press large print Christian historical fiction, 2015)
"The American Revolution is finally over, and Sophie Menzies is starved for good news. When her nearest neighbor, General Seamus Ogilvy, finally comes home to Tall Acre, she hopes it is a sign of better days to come. But the general is now a widower with a small daughter in desperate need of a mother. Nearly destitute, Sophie agrees to marry Seamus and become the mistress of Tall Acre in what seems a safe, sensible arrangement. But when a woman from the general's past returns without warning, the ties that bind this fledgling family together will be strained to the utmost. When all is said and done, who will be the rightful mistress of Tall Acre?"--Amazon.com.